Principles of the Mechanism for Epimuscular Myofascial Loads Leading to Non-uniform Strain Distributions Along Muscle Fiber Direction: Finite Element Modeling - Pamuk, Uluç; Cankaya, Alican Onur; Yucesoy, Can A. (Frontiers in Physiology, 2020)
Sarcomere lengths and their changes are primary determinants of muscular force production. Recent studies indicate inhomogeneity of sarcomere lengths within the muscle. Studies utilizing magnetic resonance imaging analyses for quantifying local muscle tissue strains and diffusion tensor imaging analyses allowing for determination of their components along muscle fascicles show that those length changes can be nonuniform. Specifically, two questions arise regarding the muscle’s length change heterogeneities along the muscle fiber direction: (1) How can a passively lengthened muscle show also shorted regions? (2) How can an isometric contracting muscle show also lengthened parts? The aim was to assess principles of the mechanism for epimuscular myofascial loads leading to nonuniform strain distributions along muscle fiber direction, by studying isolated vs. epimuscularly connected finite element muscle models. Three models were studied: (1) isolated muscle (rat EDL muscle modeled as fully isolated from its surroundings), (2) extramuscularly connected muscle and (3) epimuscularly connected muscle (muscles modeled aiming at representing the principles of a muscle in its in vivo context including the muscle’s connections to non-muscular structures alone or together with connections to neighboring muscle, respectively). Three cases were studied: passive isometric muscle with imposed relative position change (Case I), passive lengthened muscle (Case II) and active isometric muscle with imposed relative position change (Case III). The findings indicated nonuniform strains except for zero strain in model (1) in Case I, but models (2) and (3) also showed strains opposing the imposed effect. Case I: e.g., model (3) showed shortened and lengthened sections (up to 35.3%), caused exclusively by imposed relative position change. Case II: models (2) and (3) showed also shortened sections (up to 12.7% and 19.5%, respectively). Case III: models (2) and (3) showed also lengthened sections (up to 5% and 23.4%, respectively). These effects get more pronounced with stiffer epimuscular connections. Assessments of forces exerted on the muscle by the epimuscular connections showed that such strain heterogeneities are ascribed to epimuscular myofascial loads determined by muscle relative position changes.